The relationship between secondary school students' posture disorders and shyness - Asl, Nader Shaygan; Savucu, Yüksel (Editura Universitatea din Pitesti, 2014)
In this study, it is investigated the relationship between posture disorders and shyness in middle school students. Movement is an essential element of life which is important in maintaining the physiological and psychological functions. Good posture and body position plays a vital role in mental and physical health. The statistical group composed of 17974 male students in middle school of Ardebil city, among which 378 students were selected as a sample group to participate in our research. Selecting the experimental group was first done by making a list of middle schools of Ardebil city, then 14 schools were randomly selected and according to the population of each school, the experimental group was randomly selected in order. This study is an analytical descriptive one and the results indicate the abnormality of upper-and lower- skeleton of students. The students filled out a questionnaire including general information, they their general specifications were registered including age, weight and height. Then their photos were taken in three ways of anterior, lateral and posterior standing, computer software was used to analyze the posture of students (Ergo Therapy). In the study a questionnaire of 44 items were used, including 5 scales of Likert rating scale (never, rarely, sometimes, often, and always). After gathering required information, the resulted data was analyzed by descriptive static. The normality distribution of data was performed by K-S test (Kolmogrov-Smirnof test) and the mean values, standard deviation and frequency percent were obtained through descriptive statistical methods, then the differences were resulted through deductive statistics including Chi-square ?2 and ANOVA method by SPSS 20/win software. The experimental group was shown that has at least a body abnormality of 96.3%. Prevalence of abnormality was 64.6% drooping shoulders 51.3% Kyopsis and the lowest abnormality prevalence was 1.3% a flat upper back (non-curved) 1.1% extension feet. The highest shyness frequency percent was in 97.25% extension feet and the lowest shyness frequency percent was in 63.8% genu flexum. There is a significant correlation between shyness and skeletal abnormality prevalence. The mean value of students' shyness with skeletal abnormalities is higher than that of students who lack any skeletal abnormality. The results of this study indicate that the mean value of shyness in students with the trunk abnormality is 81.18%. Also the mean value of shyness in students with upper and lower skeletal abnormalities is higher than other students. © JPES.
Keywords: Middle school students; Posture disorder; Shyness; Students